Soils within cities. Global approaches to their sustainable management - composition, properties, and functions of soils of the urban environment. GeoEcological Essays. - (:unkn) unknown (Catena, 2017)
Edited on behalf of the International Union of Soil Sciences, this book is the result of a joint effort of the international SUITMA (Soils of the Urban, Traffic, Mining and Military Areas) working group of the International Union of Soil Sciences. Thirty-four short contributions comprehensively highlight key aspects and characteristics of soils of the urban ecosystem and the problems and challenges associated with them. The authors lay out the fundamentals of soil science applied to anthropized environments (environments degraded by human activity), including composition, properties, and functions of soils of the urban environment, their pedogenic evolution, classification and mapping. Furthermore, contributions present examples of actual urban soil surveys conducted in the US, Poland, Germany and Russia. Approaches to managing soils of the urban environment with focus on brownfields, soil sealing and urban agriculture, and the management of soil sealing are described. A separate chapter is dedicated to the ecosystem services urban soils can provide, including sustaining and controlling water quality and quantity, providing C and P storage capacity, supporting biodiversity, pollution problems, and pointing out ecosystem services that even contaminated industrial and mine soils are able to provide. Soils within Cities is aimed at expanding our view of soils of our planet, and having them taken into consideration for human well-being. It provides city planners and managers with a special reference that can serve to offer citizens a better life in the long run.
Keywords: Umweltschutz; Stadt; Boden; Flächennutzung; Bodeneigenschaft; Oberfläche; Bodenschutz; Versiegelung; Ökosystem; Brachfläche; Bodenfunktion; Stadtumwelt; Bodenbelastung; Grünraum; Flächenrecycling; Bodensanierung; Stadtboden; Urban Agriculture